Seed Longevity of Soybean (Glycine max L.) Cultivars Under Lightless Storage - Muhamad, Kadapi; Nauli, Kezia; Wicaksono, Fiky Yulianto; Anas (Malaysian Applied Biology, 2024)
Soybean seeds in tropical countries are prone to rapid deterioration due to environmental condition during storage, leading to a decrease in seed quality and ultimately resulting in low potential yield. Longevity of seed during storage is influenced by genetic and environmental factors such as light. Therefore, this study aimed to determine the effect of light on the vigour of two soybean seeds cultivars (Demas 1 & Devon 1 cvs) stored for three months. The investigation was conducted from February to May 2022 at Seed Technology Laboratory, Faculty of Agriculture, Universitas Padjadjaran. A correlational method was employed to assess the relationship between seed quality of Demas 1 and Devon 1 in light and lightless storage. Furthermore, data were analyzed using correlation regression and t-test to compare the two populations. The results showed that there was a high correlation between the physical and physiological quality of seeds. There were also differences in seed response to light, and this was observed from the moisture content, weight of 100 seeds, germination rate, and simultaneous growth percentage traits. Considering the seed quality traits, Demas 1 had the best vigour value after storage in dark conditions. It is worth noting that both cultivars exhibited signs of deterioration during storage. However, the rate of deterioration was slowed down due to lightless condition.